2005
DOI: 10.1038/sj.npp.1300943
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite 1 of Protopanaxadiol-Type Saponins, an Axonal Regenerative Factor, Stimulates Teneurin-2 Linked by PI3-Kinase Cascade

Abstract: We previously showed that 20-O-b-D-glucopyranosyl-20(S)-protopanaxadiol (M1), a metabolite of protopanaxadiol-type ginseng saponins by intestinal bacteria had axonal extension activity in degenerated neurons, and improved memory disorder and synaptic loss induced by an active fragment of amyloid b, Ab(25-35). It is unknown how M1 shows these effects in neurons. To clarify the signal transduction mechanism of M1-induced axonal extension, phosphorylated proteins by M1 stimulation were identified because most cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Efficacies of Kihi-to are almost similar to those of KKT, suggesting active constituents against memory improvement may be involved in overlapped crude drugs between KKT and Kihi-to. We previously showed that one of the constituents of KKT, 20-Oβ-D-glucopyranosyl-20(S)-protopanaxadiol (M1) derived from Ginseng Radix, had axonal extension activity and improved memory disorder and synaptic loss induced by , and that M1 induced axonal outgrowth through the teneurin-2-PI3-kinase cascade (Tohda, Hashimoto, Kuboyama, & Komatsu, 2006). However, many kinds of other compounds also exist in KKT (supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 97%
“…Efficacies of Kihi-to are almost similar to those of KKT, suggesting active constituents against memory improvement may be involved in overlapped crude drugs between KKT and Kihi-to. We previously showed that one of the constituents of KKT, 20-Oβ-D-glucopyranosyl-20(S)-protopanaxadiol (M1) derived from Ginseng Radix, had axonal extension activity and improved memory disorder and synaptic loss induced by , and that M1 induced axonal outgrowth through the teneurin-2-PI3-kinase cascade (Tohda, Hashimoto, Kuboyama, & Komatsu, 2006). However, many kinds of other compounds also exist in KKT (supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we found that the herbal drug-derived steroidal sapogenins regenerated neurite atrophy and synaptic loss, leading to memory improvement in AD model mice1012. Diosgenin is also a steroidal sapogenin and a major constituent in Dioscorea rhizome and other herbal drugs, such as those from Trigonella spp., Polygonatum spp.…”
mentioning
confidence: 99%
“…1, 2, 3 However, aPPD has also been demonstrated to protect neuronal cells against glutamate and N -methyl--aspartate (NMDA)-induced excitotoxicity 4, 5 and to stimulate neuronal cell regeneration by activating the Akt pathway. 6, 7 The mechanism underlying the cell-type-dependent effects of aPPD has not yet been elucidated.…”
mentioning
confidence: 99%